He mechanisms of Grammatical cohesion and it’s impact on the textual coherence in ‘Amru Al-Nami Poetry - Samira Yousef Mohemed Abou Sowa,; Zamri Arifin, (Institut Kajian Rantau Asia Barat, 2023)
The objective of this article is to identify the mechanisms of grammatical cohesion and their role in achieving textual coherence in ‘Amru al-Nami poetry, to reveal the extent to which these mechanisms are achieved in his poetry and their ability to connect the former with the latter, and their importance in the sequence of events and ideas, which helps in understanding the text and verifying its text. In this article, the descriptive analytical method was used in defining what is meant by the term ‘mechanisms of grammatical cohesion’ and the statistical method and applying those mechanisms to evidence from developing poetry and showing the extent of their achievement. The results came to indicate that the mechanisms of grammatical cohesion formed a clear coherence, as it worked on the consistency of the poems, highlighting the poet’s linguistic stock, so the pronouns matched their references, and helped to tighten the coherence of the parts of the texts and prevent them from disintegration, removing confusion and ambiguity from many contexts, and also worked on the sequence of the text has the recipient to realize through the indicative element that the poet is talking about the main idea of the text. The denotational and relative nouns also contributed to the cohesion of the text. These terms brought about consistency between the parts of the poem and helped to clarify the meaning for the recipient. It is not possible to understand what the poet is aiming at without referring to the previous or subsequent word, and this is what contributed to the existence of a pre and post text reference. In addition, the substitution contributed to linking the parts of the text, thus sparing the language to avoid repetition without prejudice to the meaning that the poet wants to convey to the recipient accurately. The deletion achieved the function of abbreviation and helped the recipient fill in the gaps, depending on the preceding or subsequent uttered elements of the text. As for al-Wasl, it has achieved formal and semantic cohesion, so it worked on arranging sentences and ideas, combining indications, and benefiting from the power of reasoning.